2016
DOI: 10.1108/jcre-10-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Make it work! Creating an integrated workplace concept

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Further, that users' understandings of the concept play an important role in how it is used. Last, this emphasises the need for office design to be adjustable and adaptable by managers and users over time, as has been suggested by other authors (Ekstrand and Hansen 2016;Värlander 2012) As previous studies have shown, processes of social control or social structures that oppose the design intentions can emerge through use in response to negative effects of the office concept or space (Hirst 2011;Värlander 2012). In support of these findings, our study found practices that emerged among users to compensate for unintended consequences.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Further, that users' understandings of the concept play an important role in how it is used. Last, this emphasises the need for office design to be adjustable and adaptable by managers and users over time, as has been suggested by other authors (Ekstrand and Hansen 2016;Värlander 2012) As previous studies have shown, processes of social control or social structures that oppose the design intentions can emerge through use in response to negative effects of the office concept or space (Hirst 2011;Värlander 2012). In support of these findings, our study found practices that emerged among users to compensate for unintended consequences.…”
Section: Discussionsupporting
confidence: 85%
“…In spatial terms, flexible office concepts employ strategies such as open-plan layouts, standardisation, free seating and clean desk policies, and focus on providing varied and attractive spaces for work and teamwork (Van Der Voordt 2004). Integrating an organisational perspective, it has been argued that organisational, cultural and managerial aspects should be aligned in the office concept to ensure flexibility (Ekstrand and Hansen 2016;Skogland 2017) and that the implementation process should aim at reducing user resistance (Brunia et al 2016).…”
Section: Flexible Office Concepts: Linking Organisational and Spatialmentioning
confidence: 99%
“…Perceiving an innovation as difficult and complex to use leads to its rejection among users (Davis, 1989;Rogers, 1995). Other complexities identified in the literature on A-FOs concern difficulties to find colleagues and colocate (Ekstrand & Karsten Hansen, 2016). However, due to the high ratio of workstations per employee and the employees' workstation choices in proximity to each other, these complexities neither were observed nor mentioned by the participants.…”
Section: Complexitymentioning
confidence: 66%
“…Since individuals' behavioural responses are limited by their knowledge on how to use the innovation, individual knowledge on how to use the innovation is critical (Hall & Hord, 2015). Assessing employees' knowledge is new in the ABW field but this is an important cognitive response since studies have found that employees lack knowledge in aspects such as the adjustment of their furniture and knowledge on the appropriate uses of certain workspaces (Been et al, 2015;Ekstrand, 2016;Ekstrand & Hansen, 2016;Voordt, 2004b). Similar to existing ABW studies, employees' perceived support for each activity conducted at each workspace also indicates their cognitive acceptance of the ABW (For example, Appel-Meulenbroek et al, 2016;Brunia et al, 2016).…”
Section: Cognitive Acceptance Responsesmentioning
confidence: 99%